PENGARUH SIKLUS KONVERSI KAS DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN - Liliana Megawati Sindhu; Saarce Elsye Hatane (Business Accounting Review, 2018)
This study aimed to examined the direct influence of Cash Conversion Cycle and Ownership Structure on Firm Value. The sample constituted of 116 manufacture companies listed in Indonesia Stock Exchange during the period of 2011-2016. The data were collected from annual reports, and then analyzed by using GRETL software. The result revealed that there was negative influence of cash conversion cycle on firm value, and positive influence of public ownership on firm value. However this study failed to find the influence of managerial ownership and foreign ownership on firm value.